High rate of ship strike to large whales off Chile: Historical data and proposed actions to reduce risk - Toro, Frederick; Buchan, Susannah J.; Alvarado-Rybak, Mario; Bedrinana-Romano, Luis; Garcia-Cegarra, Ana M.; Hucke-Gaete, Rodrigo; Olavarria, Carlos; Sepulveda, Maritza; Galletti-Vernazzani, Barbara; Sielfeld, Walter; Aguayo, Anelio; Capella, Juan; et al. (My University, 2025)
Ship strikes are a worldwide threat to large whales as a major cause of mortality and injury. In the Southeast Pacific, this has been poorly studied. In the last decade, an increase in ship strikes has been observed off Chile. This study assesses ship strike mortality in large whales off Chile using data on fatal strandings from the past 52 years, (1972-2023) and vessel traffic patterns. In 63 out of 226 strandings (28 %), ship strike was the direct or probable cause of mortality, i.e. the primary cause of non-natural death in whales. Fin whales (B. physalus) suffered highest total ship strikes (n = 23; 37%), followed by humpback (M. novaeangliae) (n =13; 21 %), blue whales (B. musculus) (n = 7; 11 %), sei (B. borealis) and sperm whales (P. macrocephalus) (n = 6; 10 %). Ship strikes were highest in the Regions of Valparaiso, Coquimbo, Atacama and Antofagasta (Central-Northern Chile), Los Lagos, Aysen and Magallanes (Southern Chile). Since 2013, when necropsies began to be systematically performed, an average of 5 individuals/year have been killed by ships, mostly between January and May. We review all ship strike studies globally and compare rates in Chile with those elsewhere. Based on data between 2013 and 2023, Chile is the country with the highest ship strike mortality globally; considering the entire time series since 1972, Chile ranks number six worldwide. We identify major knowledge gaps and recommend policy measures, including establishing High-Risk Areas and the implementation of shipping lanes modifications and vessel speed restrictions.
Keywords: ships strike; whales; chile; strandings; marine policy